Neutron Embrittlement of WWER Reactors: EC-Supported Projects - Ahlstrand, R.; Bieth, M.; Rieg, C. (Проблемы прочности, 2004)
Results of the implementation of programs on the evaluation of service life of reactor pressure vessels of NPP are considered with the account of neutron embrittlement. Data on strength of WWER-440 reactor pressure vessels with a high and moderate content of detrimental impurities (copper and phosphor) have been analyzed. For the welds of WWER-1000 reactor, drawbacks in the manufacture, dosimetry, and test procedures of surveillance specimens are shown. To ensure safe operations of reactor pressure vessels, new projects have been undertaken, focusing on the effect of neutron embrittlement of steel on the integrity of structures and advanced experimental methods of studying material strength.